ESTIMASI KARAKTERISTIK DINAMIS TAPAK LOKAL UNTUK KEBENCANAAN GEMPABUMI BERDASARKAN ANALISIS HVSR DAN ANALISIS SPAC DI KOTA PACITAN - , Nurisa Ummu Fauzia ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It has been done a microtremor a study in the Pacitan City located on province of east java. Pacitan city is in the line of seismotectonic active faults that cause earquake on the region. This study was conducted to estimate the dynamic characteristics of the local site effect in the Pacitan city based on the value of the dominant frequency factor, amplification factor, seismic vulnerability index, ground shear strain, shear wave velocity, and bedrock depth by using HVSR and SPAC analysis which results can provide information about the structure of the soil layer in Pacitan which can be used for basic infrastructure development and the mitigation of natural disasters, especially earthquakes. The results showed that in Pacitan City has a dominant ground frequency values of 0.05 Hz to 16.08 Hz, amplification of 1.30 to 8.30, the seismic vulnerability index ranged from 0.25 s to 654.53 s, ground shear strain of 1.93 Ã 10-5 to 5.47 Ã 10-2 and the depth of bedrock is 12.95 m to 89.85 m. The local effect distribution generally indicates that the area is quite high potential building damage due to the earthquakes. in the south of Pacitan city up towards the beach has a higher damage potential than the northern part. So the construction of buildings and important facilities areas should be built in the northern part of the city Pacitan.